Action-Specific Effects in Aviation: What Determines Judged Runway Size?. (February 2014) - Gray, Rob; Navia, José Antonio; Allsop, Jonathan
Several recent studies have shown that the performance of a skill that involves acting on a goal object can influence one's judgment of the size of that object. The present study investigated this effect in an aviation context. Novice pilots were asked to perform a series of visual approach and landing manoeuvres in a flight simulator. After each landing, participants next performed a task in which runway size was judged for different simulated altitudes. Gaze behaviour and control stick kinematics were also analyzed. There were significant relationships between judged runway size and multiple action-related variables including touchdown velocity, time fixating the runway, and the magnitude and frequency of control inputs. These findings suggest that relationship between the perception of a target object and action is not solely determined by performance success or failure but rather involves a relationship between multiple variables that reflect the actor's ability.